Effect of Capital Structure, Company Size, Profitability, and Company Growth on Company Value - Erlina Sri Rezeki; Selamet Eko Budi Santoso; Sri Wahyuni; Novi Dirgantari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of capital structure, company size, profitability, and company growth on firm value. This research and the data used are secondary data in the form of the company's annual report. In this study, the population used is energy sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample in this study was selected using a purposive sampling method and obtained 22 companies as a sample and the amount of data observed or researched was 81 data. The data analysis method in this study is multiple regression analysis using IBM SPSS Statistics version 26. The results of this study indicate that capital structure does not affect firm value, firm size has a positive effect on firm value, profitability has a positive effect on firm value, and company growth does not affect on firm value.